Synthesis of chromium and ferrochromium alloy in molten salts by the electro-reduction method - Ge X.; Jin S.; Zhang M.; Wang X.; Seetharaman S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, we successfully applied the Fray-Farthing-Chen Cambridge electro-reduction process on the preparation of chromium from chromium oxide, and for the first time, the synthesis of ferrochromium alloy from chromium oxide and iron oxide mixture and the chromite ore in molten calcium chloride. The present work systematically investigated the influences of sintered temperature of the solid precursor, electrochemical potential, electrolysis temperature and time on the products by using a set of advanced characterization techniques, including XRD and SEM/EDS analyses. In particular, our results show that this process is energy-friendly and technically-feasible for the direct extraction of ferrochromium alloy from chromite ore. Our findings thus provide useful insights for designing a novel green process to produce ferrochromium alloy from low-grade chromite ore or stainless steel slag.